A multiband and wideband frequency reconfigurable slotted bowtie antenna - Izni Husna Idris; Mohamad Rijal Hamid; Kamilia Kamardin; Mohamad Kamal A. Rahim; Huda A. Majid (Institute of Advanced Engineering and Science, 2020)
A multiband and wideband frequency reconfigurable antenna is presented. A wideband from 3.5 GHz to 9.0 GHz is achieved by introducing one stripline in the middle of a slotted bowtie antenna, whereas multiband is obtained by integrating an additional two slotted arms at the end of bowtie-shaped. As a result, the antenna operated at multiband mode (1.7 GHz and 2.6 GHz) and wideband mode (3.5 GHz to 9.0 GHz) simultaneously. The reconfigurability of the antenna is attained through switches. Five states are achieved with three pairs of switches configurations. All results are presented and discussed, including S11, current distribution, radiation pattern, and gain. The antenna is suitable to be used in multimode communication systems.